Influence of real-time information provided by a mobile phone on the management of rural water supply quality - Wilson-Jones, Toni (Department of Civil Engineering, 2016)
In South Africa, access to safe drinking water is a human right that is explicitly stated in the constitution. Most metro municipalities are meeting the drinking water quality targets, but the smaller rural environments are failing to provide water of acceptable drinking water quality. Reasons contributing to the high incidence of unacceptable water quality are the rural municipalities' inadequate institutional capacity and lack of management and monitoring of drinking water services. This study investigates the possibilities of supporting rural water service institutions to manage their remote water supply schemes better by addressing the challenge of distance monitoring. Through the creation of real-time information flow between the water service authorities and the water supply caretakers in remote villages, it is to be tested if better information can be received and the status of the rural water supply quality can be monitored. The improvement of information flow is based on introducing a mobile phone application. The hypothesis is that through improving the information flow, decisions on water supply management will be improved. Case study research was conducted in rural municipalities situated in the Northern Cape Province and Eastern Cape Province of South Africa. Four different municipalities were chosen to reveal the diverse municipal set-up and different challenges facing rural municipalities. Data was gathered through interviews conducted with the municipal mangers over a seven month period, as well as through field investigations. The findings reveal that the mobile reporting system has improved information flow from water supply caretakers to government service providers. The mobile application allowed for distance monitoring of rural water supply schemes. It has helped address the municipalities' institutional capacity problems by improving access to information relevant to decision making. Through the data records displayed on the mobile application, municipal mangers were able to track the supply caretakers' performance and subsequently hold them accountable. Through an increase in data availability, water quality failures were easily identified, resulting in improved confidence in the quality of rural water supply. The access to real-time information has improved the monitoring and communication of rural water quality. Early intervention and the management of non-compliance improved. The mobile technology provided the municipal managers with a tool to monitor their rural water supply schemes more regularly, but it also became apparent that the management of such schemes only improved if relevant action was taken based on the information received. Greater improvement was seen in municipalities where the tool was used consistently, where time was set aside to follow up on data warnings and protocols existed to follow up on non-compliance issues. Management of the resources did not improve in areas where management staff was severely overstretched and response strategies to problems were non-existent before the implementation of the tool.